FINANCIAL PERFORMANCE, CORPORATE GOVERNANCE AND SUKUK RATINGS: EVIDENCE FROM INDONESIA - Yusrialis, Yusrialis; Matareng, M.Iqbal Qard (Economic and Science Faculty of Islamic State University, 2025)
The development of the Islamic capital market in Indonesia has shown significant growth, particularly in corporate sukuk instruments. Sukuk ratings serve as an important indicator for investors in assessing the risk level and credibility of issuing companies. This study aims to analyze the effect of Profitability, Leverage, Liquidity, and Good Corporate Governance (GCG) on corporate sukuk ratings of companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. Profitability is proxied by Return on Assets (ROA), leverage by the Debt to Asset Ratio (DAR), liquidity by the Current Ratio (CR), and GCG is proxied through institutional ownership.This research employs a quantitative approach using panel data regression analysis. The sample was determined through purposive sampling based on criteria requiring companies to have issued sukuk, disclosed institutional ownership information, and published financial statements during the research period. Based on these criteria, 39 observations from 13 companies were obtained. Data analysis was conducted using the random effect model with the assistance of EViews 13 software.The results show that profitability, leverage, and liquidity do not have a significant partial effect on sukuk ratings. These financial ratios are not considered primary determinants by rating agencies, which instead focus more on the company’s long-term ability to fulfill sukuk obligations and maintain stable cash flows. Conversely, Good Corporate Governance (GCG), measured through institutional ownership, has a significant effect on sukuk ratings. Higher institutional ownership indicates stronger managerial oversight, thereby increasing rating agencies’ confidence in the company’s governance quality. Simultaneously, all four variables significantly influence sukuk ratings, indicating that rating agencies assess companies comprehensively, considering both financial performance and governance aspects. These findings highlight the important role of corporate governance in determining sukuk ratings, while short-term financial ratios are not dominant factors. This study is expected to provide valuable insights for investors, issuing companies, and future researchers in understanding the determinants of sukuk ratings in Indonesia.